A multi-objective stochastic programming model for project-oriented human-resource management optimization. Issue 4 (2nd October 2019) - Rahmanniyay, Fahimeh; Yu, Andrew Junfang
ABSTRACT: Human resource policy is one of the key factors in managing a project. The cost associated with the individuals assigned to a project and the quality of the tasks completed by the assigned individuals are two of the main concerns in developing a project team. In this study, we present a new multi-objective mathematical model for developing a project team for multi-disciplinary projects under uncertainty. The objective functions optimize cost and competency simultaneously. To cope with the uncertainty and the multiple objectives in the presented model, we applied the two-stage stochastic programming approach and the Augmented Epsilon Constraint Method, respectively. The presented model and its solution methodology can be applied to different types of projects. In this study, a project that involves an overhaul of a set of aircrafts is presented as a case study.